1999
DOI: 10.1038/emm.1999.13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ras/ERK-dependent pathway in the erythroid differentiation of K562 cells

Abstract: The chronic myelogenous leukemic K562 cell line carrying Bcr-Abl tyrosine kinase is considered as pluripotent hematopoietic progenitor cells expressing markers for erythroid, granulocytic, monocytic, and megakaryocytic lineages. Here we investigated the signaling modulations required for induction of erythroid differentiation of K562 cells. When the K562 cells were treated with herbimycin A (an inhibitor of protein tyrosine kinase), r a s antisense oligonucleotide, and PD98059 (a specific inhibitor of MEK), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…It should be emphasized, however, that the physiological relevance of these ®ndings with SKT6 cells to the normal erythroid di erentiation in vivo remains to be established in further studies. In fact, in a human chronic myelogenous leukemia cell line K562 which carries Philadelphia (BCR ± ABL) translocation, exogenous introduction of an activated ras gene was found to induce, rather than inhibit, erythroid di erentiation (Kang et al, 1999), suggesting that the contribution of certain signaling molecule can be quite di erent depending on genetic make-up of the cells under study.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized, however, that the physiological relevance of these ®ndings with SKT6 cells to the normal erythroid di erentiation in vivo remains to be established in further studies. In fact, in a human chronic myelogenous leukemia cell line K562 which carries Philadelphia (BCR ± ABL) translocation, exogenous introduction of an activated ras gene was found to induce, rather than inhibit, erythroid di erentiation (Kang et al, 1999), suggesting that the contribution of certain signaling molecule can be quite di erent depending on genetic make-up of the cells under study.…”
Section: Discussionmentioning
confidence: 99%
“…Erythroid differentiation is also associated with changes in MAP-kinase signaling. 8,9 Therefore we asked whether modulation of HePTP expression would have any effect on the erythroid differentiation of K562 cells. For this purpose, we treated our various K562 cell lines with the kinase inhibitor Herbimycin A which induces erythroid differentiation (Ref.…”
Section: Changes In Heptp Expression Affect Erythroid Differentiationmentioning
confidence: 99%
“…9 Briefly, K562 cells were seeded at 5 × 10 4 cells per well in 12-well plates in complete medium. To induce erythroid differentiation cells were treated with the kinase inhibitor Herbimycin A (Sigma, St Louis, MO, USA) at a final concentration of 0.2 M. After 4 days the cells were washed with PBS and incubated with an equal volume of benzidine staining solution.…”
Section: Erythroid Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent autophosphorylation of the receptors or their phosphorylation by receptor-associated protein kinases has been speculated to induce the activation of MAPK cascade including ERK and JNK (Pomerance et al, 1998). It was suggested that the dynamic balance between ERK and JNKs or p38 and the duration of MAPK activation would be important in determining the final cellular fate (Xia et al, 1995;Marshall, 1995;Chen et al, 1996;Kang et al, 1999). Differential effect of ethanol on the growth factorstimulated ERK and JNK might be another determinant for the final effect of ethanol on cell proliferation.…”
Section: Discussionmentioning
confidence: 99%